Cross-border venture capital investments: The impact of foreignness on returns. Issue 5 (July 2018) - Buchner, Axel; Espenlaub, Susanne; Khurshed, Arif; Mohamed, Abdulkadir
Abstract Against the background of the growing internationalization of venture capital (VC) investing, this is the first global comparison of the returns generated by individual domestic and cross-border deals. We examine investments worldwide during 1971–2009 and find that cross-border investments significantly underperform compared with equivalent domestic investments. Returns are negatively affected by geographic distances, cultural disparities, and institutional differences between the home and host countries. Returns on cross-border and domestic deals also decline after the late 1990s. International portfolio diversification and the saturation of domestic markets may explain why VC investors make cross-border investments despite poor expected returns. Résumé Dans le contexte de l'internationalisation croissante de l'investissement en capital risque (CR), c'est la première comparaison globale des rendements générés par les opérations individuelles domestiques et transfrontalières. Nous examinons les investissements dans le monde entre 1971 et 2009 et nous constatons que les investissements transfrontaliers sont moins performants que les investissements domestiques équivalents. Les rendements sont négativement affectés par les distances géographiques, les disparités culturelles et les différences institutionnelles entre les pays d'origine et les pays d'accueil. Les rendements sur les opérations transfrontalières et domestiques diminuent aussi après la fin des années 1990. La diversification internationale des portefeuilles et la saturation des marchés domestiques peuvent expliquer pourquoi les investisseurs en CR effectuent des investissements transfrontaliers malgré les faibles rendements attendus. Resumen En el contexto del aumento de la internacionalización de la inversión en capital de riesgo (VC), esta es la primera comparación global de los rendimientos generados por acuerdos individuales domésticos y transfronterizos. Examinamos los acuerdos en todo el mundo entre 1971 y 2009 y encontramos que las inversiones transfronterizas tuvieron un rendimiento pobre comparado con el equivalente a las inversiones nacionales. Los retornos son negativamente afectados por las distancias geográficas, las disparidades culturales y las diferencias institucionales entre los países de origen y los anfitriones. Los retornos de los acuerdos transfronterizos y los acuerdos domésticos también disminuyen después de finales de los años noventa. La diversificación del portafolio internacional y la saturación de los mercados domésticos pueden explicar por qué los inversionistas de capital de riesgo realizan inversiones transfronterizas a pesar de los pobres resultados esperados. Resumo No contexto da crescente internacionalização do investimento em capital de risco (VC), esta é a primeira comparação global dos retornos gerados por negócios domésticos e transfronteiriços individuais. Examinamos investimentos em todo o mundo de 1971 a 2009 e descobrimos que os investimentos transfronteiriços são significativamente inferiores em comparação com investimentos domésticos equivalentes. Os retornos são negativamente afetados pelas distâncias geográficas, disparidades culturais e diferenças institucionais entre os países de origem e de acolhimento. Os retornos em negócios transfronteiriços e domésticos também diminuem após o final da década de 1990. A diversificação de carteira internacional e a saturação dos mercados domésticos podem explicar por que os investidores da VC fazem investimentos transfronteiriços apesar dos retornos esperados ruins. 摘要 在风险投资(VC)国际化增加的背景下, 这是国内和跨境交易个体收益的首次全球比较。我们研究了1971年至2009年间的全球投资情况, 发现跨境投资显著落后于同等的国内投资。收益受到地理距离、文化差距以及家庭与东道国之间的制度差异的负面影响。自20世纪90年代后期以来, 跨境和国内交易的收益也在下降。国际投资组合的多元化和国内市场的饱和可能解释了为什么风险投资者进行跨境投资, 尽管预期收益不佳。